Efeito imunomodulatório da saliva de Amblyomma sculptum durante a infecção por Toxoplasma gondii - Costa, Mylla Spirandelli da (2016)
Background: The pathogenicity of Toxoplasma gondii varies according to the specie of host infected and any warm-blooded animal can serve as an intermediate host for the parasite. Amblyomma sculptum has a complex molecular saliva composition in order to maintain high levels of infestation, being capable of suppress Th1 type cytokines, while increasing anti-inflammatory cytokines. Methods: Saliva was pooled from engorged female ticks and its immunomodulatory effects were tested in mice during infection with T. gondii. Increased susceptibility of mice exposed to saliva was assessed by survival analysis, histopathology of target organs, parasite burden, cytokines quantification and specific quantification of total IgG. Results: Mice exposed to A. sculptum saliva had worse clinical condition resulted of T. gondii infection due to a low percent of survival and areas of necrosis in liver. Parasitism in lungs was higher in comparison with mice not exposed to saliva. Additionally, saliva exposure induce higher production of IL-6 while reduce TNF production in peritoneal fluid. Surprisingly, there was no difference in production of IL-10 and IFN-γ in peritoneal lavage and liver and lungs homogenate, otherwise during antigenic recall, spleen cells derived from saliva exposed mice increased levels of IL-10 and reduce IFN-γ production, after stimulation with T. gondii tachyzoites. No significant differences were obtained in specific antibody production of T. gondii. Conclusions: The exposure to A. sculptum saliva increases susceptibility of mice infected with T. gondii, by an organ-specific immune response, thus enhancing replication capacity of protozoan during an earlier acute of infection.